2013
DOI: 10.1080/09658211.2013.795976
|View full text |Cite
|
Sign up to set email alerts
|

Inferential false memories of events: Negative consequences protect from distortions when the events are free from further elaboration

Abstract: The present experiment was conducted to investigate whether negative emotionally charged and arousing content of to-be-remembered scripted material would affect propensity towards memory distortions. We further investigated whether elaboration of the studied material through free recall would affect the magnitude of memory errors. In this study participants saw eight scripts. Each of the scripts included an effect of an action, the cause of which was not presented. Effects were either negatively emotional or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…(12, 51)], in reporting new pictures as old. Table 2 shows the mean proportions of causal and plausible errors.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(12, 51)], in reporting new pictures as old. Table 2 shows the mean proportions of causal and plausible errors.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies sustain that false memories depend on semantic elaboration since false memories tend to increase as the semantic elaboration of to-be-remembered information increases (11, 12). Moreover, studies on text comprehension have amply demonstrated that when reading stories, people seek to identify factors that link characters and events [e.g., Ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a witness context, the stimuli to be remembered are often highly emotional in nature, rendering it important to investigate how earwitness testimonies of neutral material compare to the memory of emotional stimuli. Numerous studies have yielded robust results indicating that emotional memories are more detailed and more resilient to forgetting than neutral memories (Bradley & Lang, ; Mirandola, Toffalini, Grassano, Cornoldi, & Melinder, ; Putman, van Honk, Kessels, Mulder, & Koppeschaar, ). This is especially true for central aspects of an event, compared to more peripheral information (Baugerud & Melinder, ; Kim, Vossel, & Gamer, ; for a review see Christianson, ).…”
Section: Auditory Memorymentioning
confidence: 99%